The relationship between workaholism, depressive symptoms and job burnout among employees in the central region of Malaysia - Fazliyana Mohd Nazir; Nurul Ain Hidayah Abas (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the relationship between workaholism and depressive symptoms as well as the relationship between workaholism and job burnout among workers. The study employed a cross-sectional quantitative survey design in which the data collected by using an online survey method. Dutch Work Addiction Scale (DUWAS-10), Major Depression Inventory (MDI), Oldenburg Burnout Inventory (OLBI) were used in this study. A data from N=146 workers in Selangor, Putrajaya and Kuala Lumpur (n = 93 female, n = 53 male) were gathered and analysed. Pearson’s correlation analysis revealed that there was a positive correlation between workaholism and depressive symptoms (r (146) = 0.194, p = 0.019). It was found that there was significant relationship between workaholism and depressive symptoms among workers, which raises the possibility that the increase level of workaholism also increase and depressive symptoms among workers or vice versa. It was also found out there was no significant relationship between workaholism and job burnout, even though the result shows there was negative correlation between workaholism and job burnout (r (146) = -0.036, p = 0.667). This raises the possibility that increase the workaholism level does not necessarily lowers the job burnout among workers or vice versa.